Contracts and the Implied Freedom of Political Communication. (March 2021) - McCabe, Patrick
This article considers the phenomenon of contractually-imposed restraints on political communication. Such restraints often incidentally arise from broad limits on out-of-hours conduct imposed by employment contracts or from confidentiality or non-disparagement clauses in deeds of settlement. It is argued that the implied freedom of political communication has work to do in relation to at least some categories of such restraints. The various objections to that view are examined and it is argued those objections are not compelling. The article analyses the question of how the implied freedom would operate in respect of contracts that impermissibly burden freedom of political communication, and suggests that this may be achieved by developing the common law of contract to accomodate a doctrine similar to the doctrine governing unreasonable restraints of trade.